Caracterização da distribuição potencial de Lonchophylla dekeyseri Taddei, Vizotto & Sazima, 1983 (Chiroptera: Phyllostomidae) - Del Sarto-Oliveira, Lucas Laboissieri (2020)
This dissertation was organized in two parts: an introductory section for previous understanding of objective and methods treated in the manuscript, and another section containing the manuscript in full. The main objective is the description of Lonchophylla dekeyseri potential distribution, in order to subsidize measures for conservation of this nectarivorous bat, endemic from Cerrado, strictly associated with the cave environments and in danger of nature extinction. Despite, will be showed a methodological approach in multivariate analysis for description of potential distribution. To guide the necessary steps to fulfill the main objective, two ecological questions were elaborated: 1- What are the limits of L. dekeyseri geographic distribution? 2- What are the preponderant environmental variables for this distribution? To answer the first question, a modeling of potential distribution was carried out using six environmental variables and, thus, environmental variables were selected those that attenuate the Cerrado climate and relief. At each point of presence one pseudoabsence was sampled in equidistant points and based in environmental filters, in order to target as samples in focal areas of low suitability for occurrence this specie. The projections from the environmental to the geographic space occurred through five algorithms, concatenated according to the ensemble technique. To answer the second question, the potential distribution was tested by a generalized linear model (GLM) in function of 25 independent environmental variables (predictors), the same being grouped in: karst regions, soils, climate, land use and slope. Among all the predictive variables indexed in the GLM, those that have a greater positive effect on the potential distribution of L. dekeyseri are pastures, but mainly some regions of Central Brazil. Due to the degree of threat this specie, the caves used as shelter must be fully preserved. These and other actions for the conservation permeate the maintenance of biological diversity in the Cerrado, since L. dekeyseri shows great affinity for primary and secondary successional plant species (Piper sp., Cecropia sp., Bauhinia sp., Pseudobombax sp. and Lafoensia sp.).